Menghasilkan Lulusan Kreatif Melalui Pembelajaran Berbasis Masalah Kontekstual: creative thinking: contextual problem-based learning - Widodo, Suryo (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2017)
University development is inseparable from innovation. Innovations in various university components are aimed at producing graduates of the same quality. Quality graduates are produced through quality and measurable processes. Qualified graduates not only have intellectual intelligence which is indicated by high achievement index. Graduates of quality can also be demonstrated by the creative thinking ability of graduates in solving problems. Graduates creative one can be generated through contextual problem-based learning. Keywords: creative thinking, contextual problem-based learning